2004
DOI: 10.1002/cncr.20650
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of breast carcinoma in patients with clinically negative axillary lymph nodes using radiotherapy versus axillary dissection

Abstract: A series of new polyimides was prepared by reacting 2,6‐diaminopyridine with various aromatic dianhydrides in DMF in 1 : 1 mole ratio. All the resulting polyimides were readily soluble in organic solvents such as dimethylformamide, N,N‐dimethylacetamide, pyridine, m‐cresol, THF, etc. They also show good film‐forming ability. The polyimides exhibit good thermal stability and mechanical properties. The polymers have high Tg in the range of 252–296°C. The inherent viscosities of the polymers vary from 0.81 to 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…We have previously reported a retrospective analysis of the results of treatment with AxD versus AxR in these patients. 106 The results revealed that the 10-year overall survival rates for patients with T1 tumors were 94.7% in the AxD group and 92.7% in the AxR group; the corresponding rates for those with T2 tumors were 92.5% in the AxD group and 89.1% in the AxR group. For those with T1-2N0 tumors, the survival rate was similar in the AxD and AxR groups (Fig.…”
Section: Review Of Treatment Outcomementioning
confidence: 94%
“…We have previously reported a retrospective analysis of the results of treatment with AxD versus AxR in these patients. 106 The results revealed that the 10-year overall survival rates for patients with T1 tumors were 94.7% in the AxD group and 92.7% in the AxR group; the corresponding rates for those with T2 tumors were 92.5% in the AxD group and 89.1% in the AxR group. For those with T1-2N0 tumors, the survival rate was similar in the AxD and AxR groups (Fig.…”
Section: Review Of Treatment Outcomementioning
confidence: 94%
“…Since 1988, we began to substitute ALNI for ALND in patients with cN0 disease. 3 From 2001, we introduced SLNB without changing our policy to preserve the axilla. Patients with a negative SLNB usually received ALNI by extended tangential fields, and those with a positive SLNB mainly received RNI by an additional third field to the supraclavicular fossa.…”
Section: Patientsmentioning
confidence: 99%
“…In 2004, we reported that patients with cN0 were safely treated with axillary lymph node irradiation (ALNI). 3 With a longer follow-up time, we analyzed whether ALNI could control cN0 disease, including those with a positive SLNB. We also calculated additional risks of having more positive nodes after a positive SLNB to estimate the possible benefit of RNI.…”
Section: Introductionmentioning
confidence: 99%
“…1). Since 1988, we have been substituting axillary lymph node irradiation for ALND in patients with cN0 disease [5]. In 1999, we began to increase the use of high tangential irradiation for these patients, followed by the introduction of SLNB, without changing our policy to preserve the axilla [6].…”
Section: Methodsmentioning
confidence: 99%
“…However, few data exist on the correlation between technical observations and clinical outcomes. We have reported that patients with cN0 disease were safely treated with axillary lymph node irradiation without ALND [5,6]. In 2004, we began to implement computed tomography (CT)-based 3-dimensional (3-D) treatment planning using a field-in-field technique to improve the dose distribution of both the breast and the axilla [7].…”
Section: Introductionmentioning
confidence: 99%